TRX AND BATTLE ROPE TRAINING AND ITS EFFECT TO DEVELOP CERTAIN PHYSICAL ABILITIES AND LUNGE SKILL FOR YOUNG FENCERS - Owaid, Sajjad Nasser (Universitas Negeri Jakarta, 2025)
Background. Fencing is a sport that has recently been characterized by progress and development in all its aspects, especially in developing its players and their technical and skill levels, and the aspects related to the physical, tactical, skill and psychological training process, as the various modern training methods and techniques have multiplied in accordance with the physical and skill characteristics of this sport and aimed at achieving progress over the competitor and winning Objectives. The researcher conducted this current study to prepare a special training program that uses suspension ropes. TRX and Battle Rope training exercises were used to identify their impact to develop certain physical attributes and fencing skills among young players. Method. The researcher conducted this current study to prepare a special training program that uses suspension ropes. TRX and Battle Rope training exercises were used to identify their impact to develop certain physical attributes and fencing skills among young players. Results Results showed that training program prepared by the researcher using TRX, Battle Rope has a clear effect on some specific physical attributes selected for purpose of current research, there are statistically significant differences between pre-tests and post-tests for physical attributes power of arms and flexibility in favor of post-tests, training program prepared by the researcher using TRX, Battle Rope has a clear effect on raising performance level of the thrusting skill in fencing game. Conclusion. Based on these findings, the researcher recommends training program developed by this study was used to prepare young players and other categories in fencing to develop their physical and technical abilities, this training program can also be used to develop and improve specific physical abilities and technical skills of other sports.